Influence of a Sport Education season on motivational strategies in High School students: A Self-Determination Theory-based perspective - JESUS MEDINA-CASAUBÓN; Rafael BURGUEÑO (Federación Extremeña de Balonmano; University of Extremadura, 2017)
From Self-Determination Theory, the present research aimed to examine the influence of Sport Education on teacher motivational strategies in High School students in Physical Education class. The participants were 44 High School students (22 men and 22 women, Mage = 16.32, SD = 0.57). The design was a quasi-experimental study with pre- and post-test measures and intra- and -inter-group analysis. The intervention program consisted of 12 sessions of basketball both for the experimental group that developed Sport Education and for control group that developed a traditional teaching. The results reflected that Sport Education improved significantly autonomy support and structure both in the inter-group analysis and the intra-group analysis. However, there were no significant differences in involvement neither the inter-group analysis nor the intra-group. In its conclusion, Sport Education represents a model-based practice that fosters the development of the autonomy support and structure perception during the sport teaching-learning process in the school setting, which might arouse the High School student's interest for regular sport in the free time.